A 3 month pilot of the distress thermometer within community specialist palliative care services. Issue 2 (1st September 2011) - Thomas, Andy
Abstract : Introduction: The Distress Thermometer (DT) as a brief holistic screening and assessment tool has been introduced, validated and widely adopted within Oncology Services and cancer networks internationally. Supportive and palliative care guidance recommends the use of a screening tool to identify and signpost appropriate services. Aim: To modify the existing distress thermometer to fit hospice and palliative care needs, and pilot within specialist community palliative care services. Method: A working party of individuals providing nursing, emotional, psychological and spiritual support within the specialist palliative care service formed to amend the DT to fit the needs of community palliative patients. The tool was piloted by two community clinical nurse specialists (CCNS) and qualitative information collated regarding the tools appropriateness. Furthermore both qualitative patient and nurse experience was considered. Patient demographic and illness information was gathered as a possible variable influencing appropriateness of use. Finally DT training was delivered to all hospice inpatient health professionals and evaluations collected regarding the appropriateness of the DT's use with new inpatient admissions. Results: Of the 63 new referrals to two CCNS, 21 completed the tool. No age / malignant versus Non-malignant difference in those able/willing to complete the tool were identified. Qualitative experiential information supported the use of the tool within the community setting. Difficulties with usability were identified from both perspectives. Training evaluations were favourable with inpatient staff recommending the DT's use as part of the hospice admission process. Discussion: There are relative benefits and drawbacks of adopting this tool from both patient and nurse perspectives. However, the modified DT appeared to meet service needs. The training format and evaluations will be discussed in detail. Conclusion: Both pilot and training feedback supports the use of the DT within this palliative care service.